Distribución y densidad de poblaciones del gorrión común (Passer domesticus ; Aves: Ploceidae) en Costa Rica - Reynolds, Jenny (1982)
The introduced European house sparrow (Passer domesticus), presently expanding its New World range, invaded Costa Rica in 1974 or early 1975. Between 1980 and 1981 we studied the distribution of this species in Costa Rica, estimating the size of established populations and attempting to relate these factors to various ecological parameters. The house sparrow is now found practically throughout the country in settled areas, which are ecologically varied. Members of the species are almost always established at the center of towns, around parks and "plazas". There is a positive correlation between the size of the colonies and the human population density (r=0.63; p < 0.01) and a negative correlation between the house sparrow population densities and the annual rainfall (r=0.30; p < 0.05).